Performance Measurement of the Business Process Outsourcing Sector in Kenya: Balance Scorecard Approach - Kinyua, Jesse; Mburugu, Kirema; Nyambura, Chege (Academic Research Publishing Group, 2020)
The aim of this study is to investigate the performance measurement of the business process outsourcing sector in Kenya using the balanced scorecard approach. The components of the approach include financial, internal processes, customers, learning and growth. The study was carried out in all the registered business process outsourcing companies in Kenya and questionnaires administered to the marketing managers of the respective companies. To analyze data, descriptive statistics and Kruskal Wallis Test were used. Descriptive statistics was used to ascertain the view of the performance of the sector by use of means and standard deviations. Kruskal Wallis Test was used to obtain the perception of the respondents on the use of the four balanced scorecard perspectives in their companies. The study established that the business process outsourcing sector in Kenya used the balanced scorecard that included both financial and non- financial measures. However, they tended to lean more on the use of financial measures. This paper, therefore, recommends the use of non- financial measures to measure performance too.
Keywords: Performance measurement; Balanced scorecard; Performance; Business process outsourcing; Kenya